Are health claims in aging-related functional food packages different from those of general functional foods? Content analysis of food packaging from Taiwan - Liu, Chih-Chi; Lin, Hung-Chou (Frontiers in Public Health, 2024)
Given the challenges of aging populations, both in Taiwan and globally, issues related to older consumers need more attention. According to surveys in Taiwan, food is one of the most important consumer products for older adults. In recent years, functional foods have become popular, often using health claims as a promotional tool. Therefore, this study has investigated food product packaging in common retail channels in Taiwan by conducting a content analysis of all items with health claims (160 samples). This study specifically compared products related to aging and those unrelated to aging. The results revealed that more than half the participants with health claims did not provide specific descriptions of their health effects. Furthermore, products related to aging often included health terms and claims to supplement with specific nutrients in their health claims. This study has aimed to offer recommendations for educating older consumers, regulating health claims in food advertising, promoting an age-friendly consumer environment, and consumer protection.